1998
DOI: 10.1002/(sici)1097-0266(1998110)19:11<1029::aid-smj992>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Do strategic groups exist? an economic framework for analysis

Abstract: This paper offers a framework and methodology for resolving the question regarding the existence of strategic groups. We say that a strategic group exists if characteristics of the group affect firm performance independently of firm‐level and industry‐level effects. We argue that group‐level effects are a byproduct of strategic interactions among members, and develop an empirical testing model, based on the ‘New Economics of Industrial Organization,’ to distinguish true group effects from spurious effects. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(178 citation statements)
references
References 37 publications
4
170
0
4
Order By: Relevance
“…A third group is relatively small research and development firms focused solely on one or a few therapeutics, often through alliances with big pharma firms. The long-studied question of whether strategic groups exist and, if they do, how they affect firm performance remains central in the literature (Dranove, Peteraf & Shanley, 1998). A newer theme of strategic groups as referents has also emerged.…”
Section: Strategic Groupsmentioning
confidence: 99%
“…A third group is relatively small research and development firms focused solely on one or a few therapeutics, often through alliances with big pharma firms. The long-studied question of whether strategic groups exist and, if they do, how they affect firm performance remains central in the literature (Dranove, Peteraf & Shanley, 1998). A newer theme of strategic groups as referents has also emerged.…”
Section: Strategic Groupsmentioning
confidence: 99%
“…e.g. Dranove, Peteraf, & Shanley, 1998;Flavian & Polo, 1999;DeSarbo et al, 2008). Main competitors are those who are active in the same strategic group, i.e.…”
Section: Strategic Situation Analysismentioning
confidence: 99%
“…Along these lines, recent studies have integrated mobility barriers into a new theorization of the strategic group, one based on members' strategic interactions. Thus, Dranove et al (1998) focus on the performance effects of intra-group behavior. Group-level effects on performance derive from the market power, efficiency, or differentiation produced by the members' strategic interactions.…”
Section: Theory and Research Hypothesesmentioning
confidence: 99%
“…Nevertheless, researchers have suggested that the fundamental question relates not to comparisons of inter-and intra-group rivalry, but rather to how groups act competitively (see Smith, Grimm, and Wally, 1997). These researchers point out that competition and collusion are not mutually exclusive and that a variety of combinations of collective and competitive actions can exist simultaneously (Dranove, Peteraf, and Shanley, 1998).…”
Section: Introductionmentioning
confidence: 99%